MAKNA ESTETIK PADA BENTUK DAN FUNGSI PERTUNJUKAN TOPENG BANJET ABAH PENDUL KAB.KARAWANG - Hartono Rudi; Rudi Rudi Hartono (Program Studi Ilmu Komunikasi, 2021)
Abstract: This article examines the aesthetic meaning of Abah Pendul's Banjet Mask Show which was born from the ideas or ideas of the community, in this case folk theater performances live and develop in the midst of their society, of course, have form and function. The approach used is the semiotic structuralism approach of the Levi-Strauss model which describes an object of study structurally through two sides, namely the outer structure known as the surface structure and the inner structure known as the deep structure. Performances in the community where the Banjet Mask is located and cultural communication events occur in the social interaction between the show and the audience. The purpose of this article is to explore the aesthetic meaning of the Abah Pendul Banjet Mask show. The importance of this research is to determine the correlations of the aesthetic meaning of performing arts. The research method used is qualitative by referring to the structure pattern of the form and function of the performance which is descriptive narrative with triangulation and documentation of performances. In the results of the description of the performance structure, parsing, analyzing and explaining the aesthetic meaning in the performing arts of the Banjet Abah Pendul Mask in the Karawang community.